Molecular recognition of carbamazepine polymorph - Norazila, Md Tahar (2013)
The research is about the molecular dynamic simulation of carbamazepine by using the material studio software. In this research, for the experimental section we used two types of solvent that is ethanol, and acetone to observe the affect of the different types of solvent toward the polymorphs form and the formation of the H-bond and only ethanol used for simulation due to several problem occurs during this research. The objective of this research is to study the effect of various solvents on carbamazepine crystal. MD simulation is performed using Material Studio for ethanol and carbamazepine by applying COMPASS Force Field together with Forcite and Amourphous Cell Module. The dynamics run for pure solvent is performed initially in NVE ensemble at 200 ps and followed by NPT ensemble at 100-200 ps. The experimental section, amount mass of carbamazepine mixed together with 3ml volume of different types of solvent until excess appeared and analysis with FTIR. From the trajectory files, the density, radial distribution function (rdf) and diffusion coefficient were analyzed and calculated. It is expected that MD simulation able to correlate rdf with the specific functional group in solvents structure. Based on the rdf, the probabilities of finding specific intermolecular interactions of hydrogen bond which is a relatively strong form of intermolecular attraction in specific solvents can be assessed same goes to experimental result which shows different trend H-bond formed by using different types of solvent. It is a type of attractive intermolecular force that exists between two partial electric charges of opposite polarity. The difference atomic interaction from the rdf trends show that the type of solvent use in carbamazepine crystallization process may lead to the polymorphism.